SOLUSI PERSAMAAN DIFUSIVITAS ALIRAN FLUIDA MINYAK PADA RESERVOIR DAN MODIFIKASINYA UNTUK UJI ALIR (PRESSURE DRAWDOWN TEST) DAN UJI TUTUP (PRESSURE BUILDUP TEST) - Hardiyanto Hardiyanto; Lilik Hendrajaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Pressure transient of oil in reservoir can be obtained from the solution diffusivity equation. To find a solution of this diffusivity equation takes two boundary conditions as space dimension and one dimension of the initial state as a condition for the time dimension. The solution is determined by using the Laplace transform and then used as a test analysis of pressure drop in a flow test (Pressure Drawdown Test) and Pressure buildup Test. The  plot of the solution  used to prediction reservoir parameters such as permeability, skin faktor , volume of the reservoir, Dietz Shape faktor and the average pressure.Keywords: diffusion equation, the pressure transient, the drawdown-buildup.